Biomechanical Behaviors of the Orthodontic Wires - Hussain A Obaidi; Sarmad S Al-Qassar (University of Mosul, College of Dentistry, 2009)
Aims: To evaluate and compare the yield, ultimate and failure stresses of the untreated and the treatedsuper-elastic Nickel titanium and Spring hard stainless steal orthodontic arch wires with artificial salivafor one, two and four weeks. Materials and Methods: The sample consisted of four groups (10wires for each group): the control group, one, tow and four weeks of emersion in artificial salivagroups, for each of the nickel titanium and spring hard stainless steal orthodontic arch wires. The specimenswere tested with tensile procedure and plotted the load stress- strain curve, from this curve theyield, ultimate and failure stresses elasticity modulus can be calculated. The data were subjected to thedescriptive statistics, ANOVA and Duncan's analyses at p≤0.05 significant level. Results: The biomechanicalproperties (yield, ultimate and failure stresses) of Super-elastic Nickel titanium and Springhard stainless steal orthodontic arch wires demonstrated significant decrease as the immersion time inartificial saliva increased. Conclusions: The orthodontic arch wires (super-elastic nickel titanium andspring hard stainless steal) are recommended to be used intra-orally for short period to avoid reachingthe complete loss of the biomechanical properties.